Fatigue mechanisms and their implications in hypertrophy: a review - Cleary, B. (International Journal of Strength and Conditioning, 2025)
Mechanical tension, the force-velocity relationship, and high motor unit recruitment are all key factors in skeletal muscle fiber hypertrophy. Fatigue mechanisms can attenuate the hypertrophic response and can develop at any step during muscular contractions and in the post-workout period. These fatigue mechanisms can be split into central and peripheral nervous system. Fatigue physiology plays a key role in potentially modulating muscle fiber hypertrophy however they are seldom discussed together. This review aims to bridge the gap between the two domains and bring focus to the importance of appreciating and considering the role fatigue physiology can play in muscle fiber hypertrophy outcomes.